The devil is a southpaw : a novel - Hobson, Brandon (ECCO, an imprint of HarperCollins, 2025)
"Milton Muleborn has envied Matthew Echota, a talented Cherokee artist, ever since they were locked up together in a dangerous juvenile detention center in the late 1980s. Until Matthew escaped, that is. A novel within a novel, we read here Milton's dark, sometimes comic, and possibly unreliable account of the story of their childhood even as, years later, he remains jealous of Matthew's extraordinary abilities and unlikely success. Milton reveals secrets about their friendship, their families, and their nightmarish, surreal, experience of imprisonment. In revisiting the past, he explores the echoing traumas of incarceration and pride. Filled with Brandon Hobson's swirling yet visceral writing, and punctuated with original artwork, The Devil Is a Southpaw is an ambitious, elegant, and propulsive novel in the spirit of Vladimir Nabokov and Gabriel García Márquez." -- Publisher annotation.